High power microwave ablation of normal swine lung: impact of duration of energy delivery on adverse event and heat sink effects. (17th November 2018) - Kodama, Hiroshi; Ueshima, Eisuke; Gao, Song; Monette, Sebastien; Paluch, Lee-Ronn; Howk, Kreg; Erinjeri, Joseph P.; Solomon, Stephen B; Srimathveeravalli, Govindarajan
Abstract: Purpose: The purpose of this study is to assess the impact of duration of energy delivery on adverse events (AEs) and heat sink effects during high power microwave ablation (MWA) of normal swine lung. Materials and methods: High power (100 W) MWA was performed with short (2 min, 18 ablations) or long (10 min, nine ablations) duration of energy delivery in unilateral lung of swine ( n = 10). CT imaging was done prior to sacrifice at 2 or 28 d post-treatment, with additional imaging at 7 and 14 d for the latter cohort. Ablation zones were assessed with CT imaging and histopathology analysis. Differences in AEs and ablation characteristics between groups were compared with Fisher's exact test and Student's t -test, respectively. Results: There were no significant differences in formation of air-filled needle tract, cavitation, and pneumonia ( p > 0. 5 ) between the treatment groups. Intra-procedural pneumothorax requiring chest tube placement occurred in three animals. Substantial (>20%, p = 0.01) intra-procedural ablation zone distortion was observed in both groups. The presence of large airways or blood vessels did not result in heat sink effect within the ablation zones and was not indicative of reduced ablation size. Increased energy delivery yielded larger (8.9 ± 3.1 cm 3 vs. 3.4 ± 1.7 cm 3, p < 0.001) spherical ablations (sphericity: 0.70 ± 0.10 vs. 0.56 ± 0.13, p = 0.01). Conclusions: High power MWA of normal lung with longer duration of energy delivery can create larger spherical ablations, without significant differences in post-procedure AEs when compared with shorter energy delivery time.